(untitled) (International conference on multidisciplinary science, 2026)
According to estimates by experts from the World Health Organization and the International Agency for Research on Cancer (IARC), more than 500,000 new cases of kidney cancer are diagnosed worldwide each year. In 2020, kidney cancer ranked 16th among the most commonly diagnosed cancers worldwide, accounting for approximately 2.2% of all cancer diagnoses. Furthermore, kidney cancer accounts for 1.8% of all cancer-related deaths and is one of the most dangerous urological cancers, with a 5-year survival rate of 12%.